Design of multifunctional food packaging films based on carboxymethyl chitosan/polyvinyl alcohol crosslinked network by using citric acid as crosslinker. (16th September 2021) - Wen, Lishan; Liang, Yuntong; Lin, Zhenhao; Xie, Donghong; Zheng, Zhongjie; Xu, Chuanhui; Lin, Baofeng
Abstract: The application of bio-based materials such as biodegradable films for food packaging to reduce the use of non-biodegradable petroleum-based food packaging materials is of great significance to alleviate environmental pollution. Here, we use a simple and efficient method to design a multifunctional food packaging film with biodegradability, antifogging and antibacterial properties based on carboxymethyl chitosan/polyvinyl alcohol crosslinked network by using citric acid as crosslinker. The resultant films exhibited many desirable and impressive features, such as good mechanical properties, antifogging, antibacterial and biodegradable. The citric acid (CA) was used not only as multifunctional cross-linkers via hydrogen bonding with polyvinyl alcohol (PVA) and carboxymethyl chitosan (CMCS) but also as effective reinforcers to improve mechanical and antibacterial properties of the composite films. As CA contents achieved 5 wt%, the tensile strength of films increased from 21.03 MPa to 29.65 MPa, and the Young's modulus increased from 3.71 MPa to 10.87 MPa. It was found that CMCS and CA affected the crystallization situation of PVA composite films and helped to promote the soil microbial degradation of films. CA enhanced the crosslinking between PVA and CMCS, forming a crosslinked network, improving the thermal stability of the composite films and decreasing its water vapor permeability and swelling properties. More importantly, the prepared antifogging film can not only relatively delay the water loss of strawberries and cherry tomatoes, but also significantly reduce the growth of bacteria, and thus extending the shelf life. Therefore, this report provided a new solution to alleviate non-degradable plastic problem which illustrates its potential for food preservation and packaging applications. Graphical abstract: Image 1 Highlights: A multifunctional film based on a crosslinked network was designed and constructed. CA enhanced the mechanical property and made PVA/CMCS films antibacterial. CMCS and CA helped to promote the soil microbial degradation of PVA composite films. The PVA/CMCS/CA films were antifogging, antibacterial and biodegradable.